Conditions for Implementing the ICF-CY in Education: The Experience in Portugal - Sanches-Ferreira, Manuela; Silveira-Maia, Mónica; Alves, Sílvia; Simeonsson, Rune J. (Frontiers in Education, 2018)
Reflecting international trends for implementing inclusive education, Portugal enacted a special education law (Law No. 3/2008) in 2008, defining substantial changes in educational practice. One of the most important changes consisted in determining that eligibility for special education services be based on the functioning profile of students documented with the International Classification of Functioning, Disability and Health, version for children and youth (ICF-CY, WHO, 2007). The study described in this manuscript belongs to a broader project and consisted of the administration of a survey to a nationally representative sample of 551 professionals, to examine factors they considered as most influential to the perceived ease in using the ICF-CY, as well as identifying the extent to which the professional groups and the enrolment on training relates to the opinion about the use of the ICF. For sample recruitment, 414 clusters of schools were randomly selected, stratified according to the distribution of schools in the different Regional Directorates of Education in Portugal. The survey consisted of demographic questions and 49 scaled items, assessed on a 4-point Likert scale in which respondents rated: (i) the perceived ease on the ICF-CY usage; (ii) their level of knowledge on conceptual and procedural aspects inherent to the Law implementation, as well as, on regard to performed roles defined; (iii) the extent to which their schools presented conditions for collaboration; (iv) the importance of contextual variables as valued conditions for using the ICF-CY. Results showed that the establishment of mechanisms for collaboration and interdisciplinarity were central conditions to meet the comprehensiveness and rigor defining an ICF-CY based assessment. Likewise, consideration of diverse backgrounds and needs of professional groups in terms of knowledge needs to be a central requirement for implementing an ICF-CY informed approach. An important implication for training programs is to have an expanded focus on demonstrations on how the ICF-CY can be used to support the implementation of socio-ecological and inclusive perspectives.